Curved vs. flat solar air heater: Performance evaluation under diverse environmental conditions - Singh A.P.; Singh O.P. (My University, 2025)
The present study evaluates and compares the performance matrix of a curved and flat solar air heater (SAH) under diverse environmental conditions using an experimentally validated numerical model. Firstly, the optimum curvature angle for curved SAH that offers optimum thermal performance (i.e. 25°) under wide range of parameters such as Reynolds numbers (2200–6000), mass flow rate (0.0172–0.0472 kg/sm2) and solar radiation inclination angle (0–60°) has been determined. The enhancement factor (i.e. Nucurved/Nuflat) is in the range 1.5-2.2 which show that curved SAH is thermally much better than flat design. Secondly, the optimized curved SAH is then compared with flat design for 0–60° tilt anglesθ, under tranquil and windy conditions (wind velocity range: 0.5–4 m/s), respectively. Under windy condition the heat loss from SAH to surrounding is lower for curved SAH at θ = 0°, 60° in windward, 30° in leeward and 30° in tranquil- condition in comparison to flat SAH. In the extreme case θ = 60° and wind speed of 4 m/s, the percentage change in average differential pressure coefficient ΔCP is about 2% higher for curved SAH under windward while it is about 19% less in leeward condition compared to flat SAH. © 2019 Elsevier Ltd